Exploring factors that affect on cancer patients performance in social networks for informational support - Mirabolghasemi, Marva (Inderscience Enterprises Ltd., 2015)
The social network communities that promote information about cancer are able to develop an interactive environment where there are virtual relationships among cancer patients. Only a few studies have looked at the role of social network sites (SNS) for cancer patients despite their potential to deliver health messages to large audiences. Hence, there should be more rigorous research to explain the behaviour of cancer patients in SNS. This study seeks to explore the emotional, cognitive, social and technological constructs that affect the performance of cancer patients in social networks by using social cognitive theory (SCT) and task technology fit (TTF) theory. This study also aims to use a mixed method study in Mount Miriam Cancer Hospital (MMCH) and Kluang Cancer Support Group in peninsular Malaysia